Identify the immune characteristics and immunotherapy value of CD93 in the pan-cancer based on the public data sets - Guo, Aiyuan; Zhang, Jingwei; Tian, Yuqiu; Peng, Yun; Luo, Peng; Zhang, Jian; Liu, Zaoqu; Wu, Wantao; Zhang, Hao; Cheng, Quan (Frontiers in Immunology, 2022)
CD93 is a transmembrane receptor that is mainly expressed on endothelial cells. A recent study found that upregulated CD93 in tumor vessels is essential for tumor angiogenesis in several cancers. However, the mechanism remains largely unknown. This study systematically analyzed the role of CD93 in tumor immunotherapy among 33 cancers. CD93 levels and co-expression of CD93 on cancer and stromal cells were detected using public databases and multiple immunofluorescence staining. The Kaplan-Meier (KM) analysis identified the predictive value of CD93 in pan-cancer. We also explored the survival difference between mutant and WT, CNV groups, and methylation. The immune landscape of CD93 in the tumor microenvironment was analyzed using the SangerBox, TIMER 2.0, and single-cell sequencing. The immunotherapy value of CD93 was predicted through the public databases. There were significant differences in the expression of CD93 mRNA and protein levels between cancer samples and adjacent normal tissues in pan-caner. CD93 mRNA expression was associated with prognosis in most cancer types. The correlation between CD93 expression and other gene mutation status in pan-cancer were analyzed. CD93 levels significantly positively correlated with immune scores, stromal scores, estimate scores, immune infiltrates, immune checkpoints, and neoantigen levels. Additionally, single-cell sequencing revealed that CD93 is predominantly co-expressed on tumor and stromal cells, such as cancer-associated fibroblasts (CAFs), endothelial cells, neutrophils, T cells, macrophages, M1 and M2 macrophages. Several immune-related signaling pathways were enriched based on CD93 expression, including activation and migration of immune cells, focal adhesion, leukocyte transendothelial migration, oxidative phosphorylation, and complement. Multiple immunofluorescence staining displayed the co-expression of CD93 on T cells, macrophages, and M2 macrophages in these cancers. Finally, the therapeutic response of CD93 in immunotherapy cohorts and sensitive small molecules was predicted from the public datasets. CD93 is closely associated with clinical prognosis and immune infiltration in multiple tumor types. Targeting CD93 in the tumor microenvironment may be a promising therapeutic strategy for tumor immunotherapy.